Regulation of cell differentiation via synergistic self-powered stimulation and degradation behavior of a biodegradable composite piezoelectric scaffold for cartilage tissue. (December 2021) - Lai, Yen-Han; Chen, Yung-Hsin; Pal, Arnab; Chou, Syun-Hong; Chang, Shwu-Jen; Huang, E-Wen; Lin, Zong-Hong; Chen, San-Yuan
Abstract: The articular cartilage disorder at the junction mainly results from constantly repeated dynamic tension/compression effects with ageing and lack of intrinsic defect repairability. Therefore, the degradable piezoelectric scaffolds are very essential, which mimics the dynamic mechanical loading and optimizes the chondrocyte differentiation during the degradation. Here, a degradable aligned electrospun poly-L -lactic acid (PLLA) modified with graphene (rGO) and polydopamine (PDA) fibrous scaffolds with different orientations (0°, 90°) and surface morphologies (wrinkled and porous) was developed as a biocompatible and degradable piezoelectric scaffold with the self-powered tunable piezoelectricity to modulate cell behaviour and cell differentiation by tuning the degradation effect. The results show that the electrical output and mechanical properties of the composite fibrous scaffold can be improved by adding rGO and applying mechanical force along with the 90° orientation. With changing the degradation behavior, dynamic mechanical loading on the porous PLLA/rGO/PDA fibrous scaffold exhibits a significant increase in cell proliferation and secretion of extracellular matrix (ECM). More surprisingly, as extending the degradation periods to 21 days, a higher glycosaminoglycans (GAGs) synthesis was detected in prechondrogenic ATDC5 cells cultured on the degraded porous scaffold compared with that after 7 days' culture. This indicated that long-term degradation favoured promoting cell differentiation of ATDC5 towards a chondrogenic phenotype due to dynamic mechanical loading, low-intensity electrical stimulation, and interconnected porous structural morphology. In contrast, on the wrinkled PLLA/rGO/PDA fibre with a high-intensity electrical stimulation, the ALP activity significantly increased after 21 days, inducing mineralization with the differentiation of ATDC5 into osteocytes. The modulation of the degraded environment and electrical stimulation of the piezoelectric scaffold offers an effective alternative to influence cell functions, significantly improving the ECM secretion and cell differentiation. Graphical Abstract: ga1 Highlights: The modulation of cell functions has been demonstrated by the biocompatible and biodegradable PLLA/rGO/PDA scaffold. The piezoelectricity generated from the bending of the scaffold can help to increase the secretion of extracellular matrix. Structure orientation, surface morphology and degradation effect of the scaffold on cell behaviors have been Investigated. The piezoelectric and mechanical properties of the scaffold control the cell proliferation and differentiation progresses. The scaffold can provide self-powered electrical stimulation from human motions to recover the damaged cartilage.